2023
DOI: 10.1002/gps.5872
|View full text |Cite
|
Sign up to set email alerts
|

Delirium is significantly associated with hospital frailty risk score derived from administrative data

Abstract: Objectives Delirium is highly prevalent in hospitalised older adults, under‐diagnosed and associated with poor outcomes. We aim to determine (i) association of frailty measured using Hospital Frailty Risk Score (HFRS) with delirium, (ii) impact of delirium on mortality, 30‐days readmission, extended length of stay (eLOS) and cost (eCOST). Methods Retrospective cohort study was conducted on 902 older adults ≥75 years discharged from an academic tertiary hospital between March and September 2021. Data was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…More recently, a 2023 Japanese study also demonstrated the association of higher HFRS scores with higher rates of prolonged hospitalization (LOS > 15 days and LOS > 30 days) amongst 98 420 patients with pneumonia 33 . A local study of 902 patients admitted to a tertiary hospital also demonstrated that patients with delirium had higher HFRS scores and had greater 30‐day mortality (OR 2.52) and 30‐day readmission (OR 2.18) 21 . Patients with delirium were also shown to have a higher prevalence of infections such as pneumonia (37.7% vs. 25.3%) 21 …”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…More recently, a 2023 Japanese study also demonstrated the association of higher HFRS scores with higher rates of prolonged hospitalization (LOS > 15 days and LOS > 30 days) amongst 98 420 patients with pneumonia 33 . A local study of 902 patients admitted to a tertiary hospital also demonstrated that patients with delirium had higher HFRS scores and had greater 30‐day mortality (OR 2.52) and 30‐day readmission (OR 2.18) 21 . Patients with delirium were also shown to have a higher prevalence of infections such as pneumonia (37.7% vs. 25.3%) 21 …”
Section: Discussionmentioning
confidence: 96%
“…33 A local study of 902 patients admitted to a tertiary hospital also demonstrated that patients with delirium had higher HFRS scores and had greater 30-day mortality (OR 2.52) and 30-day readmission (OR 2.18). 21 Patients with delirium were also shown to have a higher prevalence of infections such as pneumonia (37.7% vs. 25.3%). 21 Our study has a number of strengths.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations